Mediation and moderation analysis of the association between physical capability and quality of life among stroke patients - Xue Yang; Hongmei Zhang; Qian Liu; Yihuan Lu; Liqing Yao (PLoS ONE, 2025)
To estimate the extent to which physical capability, depressive symptoms, balanced self-efficacy (BSE), and other risk factors, that are interrelated with stroke, influence the quality of life (QoL) in stroke survivors. A theoretical model based on Wilson and Cleary’s model tested the specific hypotheses: 1) physical capability has an indirect effect on QoL mediated by BSE; 2) physical capability has an indirect effect on QoL by depressive symptoms; 3) stroke risk factors (hypertension/diabetes/gender) moderate the above relationship. Six hundred and seventy stroke survivors were enrolled from ten different hospitals in Yunnan province from 2019 to 2021. Patients’ mental and physical function was assessed using the Brunnstrom recovery stage (BRS), mini-balance evaluation system test (Mini-BEST), Barthel index (BI), Activities-specific Balance Confidence scale (ABC), and Hamilton depression scale (HAM-D). The structural equation model (SEM) was used to test the moderated mediation model in Mplus 8.0 software. The model showed a good fit (RMSEA =  0.075, SRMR =  0.010). BSE significantly mediated the relationship between physical capability and QoL (β =  0.322, p =  0.002). Hypertension was found a significant moderator of all the direct paths from physical capability to QoL through depressive symptoms (В =  0.412, p =  0.015; В =  0.831, p =  0.020, respectively). This study provides a better insight into the relationship between physical capability and QoL via BSE in stroke survivors, which may help establish appropriate treatment for these individuals.